An assessment of the nutritional status of ART receiving HIV-orphaned and vulnerable children in South-West Nigeria (2019)
Introduction: Good nutritional status is pertinent to the optimal outcome of effective ART among children. Against this backdrop, the objective of the current study is to assess the nutritional indices of children receiving ART in South-West Nigeria. Methods: The study was cross-sectional in design. We randomly selected three urban and six rural ART sites from the ones offering ART services in Oyo state. All consented children receiving ART treatments in the aforementioned sites participated in the study. A total of 390 HIV-positive children and adolescents aged 6–18 years were interviewed using a semi-structured interviewer-administered questionnaire. Children were assessed and growth curves were constructed using the 2007 World Health Organisation (WHO) growth reference standard for children as well as adolescents. Data were presented using descriptive statistics. Results: About 52% of the children are male, 136 (34.9%) have lost at least one parent, 52 (13.3%) have lost either parent to HIV/AIDS. Among the males, 19%, 27%, and 27% were underweight, stunted and thin, respectively when compared with 17%, 23% and 23%, respectively, among females. The male and female weight-for-age average z-score were (-0.98 vs -1.04), height-for-age (-1.12 vs -1.07), and BMI-for-age (-1.19 vs -1.18). Irrespective of age, sex, parental survival, and residence, weight-for-age and BMI-for-age analysis revealed substantial underweight, with the worst outcomes being among those orphaned by HIV/AIDS. Conclusion: All nutritional indices considered in this study fell short of the WHO standard. HIV positive children in the ART sites included in this study are faced with a high burden of undernourishment despite been placed on daily ART regimens. In addition to efficient ART, interventions to ameliorate poor nutritional status is needed.